Delayed Retropubic Urethroplasty of Completely Transected Urethra Associated With Pelvic Fracture in Girls - Hosseini, Jalil; Tavakkoli Tabassi, Kamyar; Razi, Abdollah (Urology Journal, 2009)
Introduction: The objective of the present study was to evaluate the results and the complications of delayed retropubic urethroplasty of completely transected urethra associated with pelvic fracture in girls. Materials and Methods: From 2002 to 2008, a total of 7 girls with complete urethral disruption after pelvic fracture were referred to our center and all of them underwent delayed retropubic urethroplasty with end-to-end anastomosis of the urethra. Results: Seven female patients with a median age of 6 years old underwent delayed end-to-end anastomosis. The median time to surgery was 6 months from the trauma. Voiding was normal after catheter removal in all of the patients. The median follow-up was 36 months. Three patients had mild stress urinary incontinence after catheter removal. Conclusion: There are some different strategies for management of complete urethral avulsion in females who have sustained pelvic fracture, including early realignment, bladder flaps, and end-to-end anastomosis. The strategy of delayed end-to-end anastomosis urethroplasty with retropubic approach is sound and produces acceptable results. The use of flexible cystoscope and omental flap is effective in achieving continence after urethroplasty in such cases.